The HIV-1 capsid core is an opportunistic nuclear import receptor - Guangai Xue; Hyun Jae Yu; Cindy Buffone; Szu-Wei Huang; KyeongEun Lee; Shih Lin Goh; Anna T. Gres; Mehmet Hakan Guney; Stefan G. Sarafianos; Jeremy Luban; Felipe Diaz-Griffero; Vineet N. KewalRamani (Nature Communications, 2023)
Abstract The movement of viruses and other large macromolecular cargo through nuclear pore complexes (NPCs) is poorly understood. The human immunodeficiency virus type 1 (HIV-1) provides an attractive model to interrogate this process. HIV-1 capsid (CA), the chief structural component of the viral core, is a critical determinant in nuclear transport of the virus. HIV-1 interactions with NPCs are dependent on CA, which makes direct contact with nucleoporins (Nups). Here we identify Nup35, Nup153, and POM121 to coordinately support HIV-1 nuclear entry. For Nup35 and POM121, this dependence was dependent cyclophilin A (CypA) interaction with CA. Mutation of CA or removal of soluble host factors changed the interaction with the NPC. Nup35 and POM121 make direct interactions with HIV-1 CA via regions containing phenylalanine glycine motifs (FG-motifs). Collectively, these findings provide additional evidence that the HIV-1 CA core functions as a macromolecular nuclear transport receptor (NTR) that exploits soluble host factors to modulate NPC requirements during nuclear invasion.